The Impact of Immigration on the Employment Dynamics of European Regions - Anthony Edo; Cem Özgüzel (Institute of Labor Economics (IZA), 2023)
This paper provides the first evidence on the regional impact of immigration on native employment in a cross-country framework. By exploiting the richness of the European Labour Force Surveys and past censuses, we show that the rise in the share of immigrants across European regions over the 2010-2019 period had a modest impact on the employment-to-population rate of natives. However, the effects are highly uneven across regions and workers, and over time. First, the short-run estimates show adverse employment effects in response to immigration, while these effects disappear in the longer run. Second, low-educated native workers experience employment losses due to immigration, whereas high-educated ones are more likely to experience employment gains. Third, the presence of institutions that provide employment protection and high coverage of collective wage agreements exert a protective effect on native employment. Finally, economically dynamic regions can better absorb immigrant workers, resulting in little or no effect on the native workforce.
Keywords: F22; J21; J61; 330; immigration; employment; labour supply; employment dynamics